Tradição visual: políticas de conservação de acervos etnográficos a partir de práticas inclusivas - Mônica Lima de Carvalho (2020)
The artefacts of indigenous material culture draw their own style through the lightness of forms and the ephemerality of the matter and materialise the essential element of life from the natural world of organic and inorganic beings - itself through the interface of creativity. The analysis of which I write about narrates the experience of twenty years of activities in the Anthropological Museum of the Federal University of Goiás, resulting in the epistemological contribution towards the Participatory Conservation of the indigenous ethnographical collections under its guard. The indigenous material culture is essential for the managerial implementation of the methodology of participant observation through the exposure of their producers to the activities that favour the preservation of the component artefacts of these collections. The intention is to introduce the shared management of the Cultural Heritage preservation to the demand of Conservation of the indigenous ethnographic collections currently present in Brazilian anthropological museums. In theory, bringing the Indigenous to the Brazilian museums and effectively integrating them as part of the teams that act in favor of the preservation of these safeguarded collections, allowing them to opt for a spontaneous approach towards their artefacts in Technical Reserves, following the criteria of the Preventive Conservation applied to the safeguard of museum collections. The importance of the suggested theory praises the social acceptance of those who bring along the art of constructing and seeing the reality of their production in artefacts that reveal their traditional origins through the diverse creative ways of managing the indigenous ethnographic collections in the museums that meet, mainly, the interests of the Amerindians that would like to work in these institutions that storage their material cultures. This way, contributing to the demands of the documentation of the Brazilian indigenous ethnographic collections provides the possibility of the promotion of educational actions to the public and promotes, respectively, the museums that sponsor this initiative.